Population dynamics of the Asian moon scallop (Amusium pleuronectes, Linn.) around the Chang Islands, Trat Province - Jintana Nugranad (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 1990